The Relationship Between Malocclusion Perceptions of Patient and Clinician - Hasan Kamak; Murat Çağlaroğlu; Bülent Çatalbaş; Enes Tan (Galenos Yayinevi, 2012)
Aim:To evaluate the Aesthetic Component (AC), which is part of Index of Orthodontic Treatment Need (IOTN) according to the patient and the clinician's point of view and to examine whether there is a difference between them in terms of awareness according to gender and pubertal situation.Subjects and Method:The study material of 100 patients (50 males, 50 females) with mean age 13.9 consisted of pre-treatment orthodontic models and hand-wrist films. AC images used in determination of the patient and clinician perceptions of malocclusion.Results:These 100 patients gave the same score with 32 clinicians, percentage of compliance of all patients was 32.0 % and there was no statistically significant differences (p>0.05) between clinician and patient's perceptions of malocclusion. Perceptions of malocclusion was also examined according to genders, there was no statistically significant difference between female and male patients, and clinician (p>0.05). Perceptions of malocclusion was also examined according to puberta, there was only no statistically significant difference between patients in pubertal period and clinician (p>0.05), but there was statistically significant difference (p<0.05) between patients with pre-and postpubertal period, and clinician.Conclusion:Although there was not difference between perceptions of malocclusion of the genders, the patients in pubertal period were more objective, more aware of their malocclusions and dental aesthetics than the pre-and postpubertal patients So that, a greater number of this patients referred for orthodontic treatment.